Vieta's triangular array and a related family of polynomials - Neville Robbins (International Journal of Mathematics and Mathematical Sciences)
If n≥1, let the nth row of an infinite triangular array consist of entries B(n,j)=nn−j(jn−j), where 0≤j≤[12n].